A heteromeric complex containing the centromere binding factor 1 and two basic leucine zipper factors, Met4 and Met28, mediates the transcription activation of yeast sulfur metabolism. - Kuras, L (1996)
Transcription activation of sulfur metabolism in yeast is dependent on two DNA binding factors, the centromere binding factor 1 (Cbf1) and Met4. While the role of Met4 was clearly established by showing that it acts as a transcription activator, the precise function in transcription of the multi-functional factor Cbf1 remains more elusive. We report here the identification of a new transcription factor Met28 which participates in the regulation of sulfur metabolism. Cloning and sequencing of MET28 revealed that it encodes a new member of the basic leucine zipper DNA binding factor family. We also demonstrate that Met28 possesses no intrinsic transcription activation capabilities. Studies of the DNA binding characteristics of Met28 led us to identify in gel mobility assays a heteromeric complex containing Cbf1, Met4 and Met28. We further demonstrated that the presence of Cbf1 and Met4 stimulates the binding of Met28 to DNA. 'Two-hybrid' studies allowed us to carry out preliminary investigations on the binary protein-protein interactions involved in the formation of the Cbf1-Met4-Met28 complex. Our results give evidence that the leucine zippers of Met4 and Met28, along with the basic helix-loop-helix domain of Cbf1, provide the protein surfaces mediating these interactions. All these results suggest that the multi-functional factor Cbf1 functions in transcription activation by tethering specific activating factors to the DNA.